Evaluating Supply Chain Performance through Financial Metrics: A Study in a Manufacturing Industry - Saleheen, Ferdoush; Habib, Md. Mamun (International Journal of Supply Chain Management, 2024)
This empirical study is based on primary data emphasizing the importance of evaluating supply chain performance through financial metrics, each activity within the supply chain directly impacts both the top line and bottom line of a business. In today's challenging business environment, organizations must prioritize monitoring their financial performance to ensure enduring resilience. The economy of Bangladesh has encountered turbulence due to disruptions such as the aftermath of the COVID-19 pandemic and the ongoing global political unrest. These occurrences have significantly impacted the business landscape, resulting in uncertainties in both demand and supply, shifts in consumer purchasing patterns, and notable increases in the prices of essential commodities and raw materials, therefore, the overall cost of business has risen. This study investigates the consequences of various disruptions, both internal and external, on the economy, adversely affecting organizations. The ability of an organization to withstand such challenges depends on maintaining robust financial and operational performance. Given the persistent global upheaval, there is a compelling need for an innovative approach to enhance supply chain optimizations, overall operational efficiency, and meticulous budget control and variance analysis aligned with financial planning. This is crucial at a substantial level to ensure positive entries in the profit and loss account and maintain a healthy cash flow statement. This study is done based on twenty-four (24) manufacturing sectors of Bangladesh. To address these challenges, the study advocates an Integrated Supply Chain Performance Measurement (ISCPM) model. This model contributes to academia through a novel approach, demonstrating its effectiveness by employing ten attributes to evaluate supply chain performance, with a specific focus on the financial performance termed Financial Health (FH), an attribute to measure supply chain performance in an organization. The study further elaborates Financial Health attributes into five key Performance Measurement Index (PMI) which are Economic Performance, Cost, Budget Variance, Inventory, and Planning Variance —within the context of manufacturing operations, providing insights into various facets of their impact. The study significantly contributes to the industry for practitioners by bringing synergy into the framework and performance measurement attributes, ultimately adding value to the manufacturing industry.